2020
DOI: 10.21203/rs.3.rs-63585/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircTP63 Promotes Hepatocellular Carcinoma Progression by Sponging miR-155-5p and Upregulating ZBTB18

Abstract: Background: Hepatocellular carcinoma (HCC) is the leading cause of tumor-related death worldwide due to high morbidity and mortality, yet still lacking biomarkers and therapies. Circular RNAs (circRNAs) are a group of non-coding RNAs that regulate gene expression through interacting with miRNAs, implicating in the tumorigenesis and progression. A novel circRNA, circTP63, was reported to be an oncogene in HCC. However, its role in HCC remains unclear.Methods: qRT-PCR was used to assess the mRNA levels of CircTP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…CircPPP1R12A expression in A549 and H1299 cells was upregulated after Lv‐circPPP1R12A transfection (Figure 1C). Circular RNAs play a crucial part in the malignant phenotype of cancer cells, such as proliferation, invasion and migration 21–24 . For example, hsa_circ_0020095 enhances colon cancer proliferation, invasion and migration 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CircPPP1R12A expression in A549 and H1299 cells was upregulated after Lv‐circPPP1R12A transfection (Figure 1C). Circular RNAs play a crucial part in the malignant phenotype of cancer cells, such as proliferation, invasion and migration 21–24 . For example, hsa_circ_0020095 enhances colon cancer proliferation, invasion and migration 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Circular RNAs play a crucial part in the malignant phenotype of cancer cells, such as proliferation, invasion and migration. [21][22][23][24] For example, hsa_circ_0020095 enhances colon cancer proliferation, invasion and migration. 24 Hsa_circ_0022160 accelerates esophageal squamous cell proliferation, migration and invasion.…”
Section: Circppp1r12a Was Involved In Nsclc Cell Proliferationmentioning
confidence: 99%
“…It is showed that circRNA is closely associated with the recurrence-free survival (RFS) and OS of HCC by univariate and multivariate Cox regression analysis, dysregulated circRNA might be used as a prognostic factor for the selection of rational treatment regimens for HCC, due to circRNA shows stable conserved and high specificity in different tissues even the stages of disease [129]. For instance, hsa_ circ_0128298 [130], circLARP4 [131], circTP63 [132], circBIRC6 [133], hsa_circ_104348 [134] and circZNF566 [135], etc., were overexpressed in HCC tissues and cell lines. Kaplan-Meier survival analysis showed that HCC patients with circRNA high expression and had shorter overall survival than those with low expression.…”
Section: Circrna As Potential Prognostic Biomarker In Hccmentioning
confidence: 99%
“…In addition, hsa_circ_0128298 [130], circLARP4 [131] and circBIRC6 [133] were testified to be the independent prognostic factors of OS by multivariate Cox regression analysis. Moreover, studies have found that high expression of hsa_circ_0128298 was associated with vascular cancer embolus, LNM and organ metastasis; overexpression of circTP63 [132] was related to TNM stage, tumor differentiation, and LNM; circLARP4 [131] and circ-ZNF566 [135] were associated with clinicopathological features, including tumor differentiation, tumor size and TNM stage, etc., circ-BIRC6 [133] was associated with TNM stage and MVI in HCC tissues; hsa_circ_104348 [134] expression level was related to tumor size, LNM as well as TNM. Besides, univariate and multivariate Cox regression analysis showed circZKSCAN1 was an independent prognostic factor of OS and RFS by binding FMRP, and the combination of circZKSCAN1 and CCAR1 could improve the prognostic value of HCC [136].…”
Section: Circrna As Potential Prognostic Biomarker In Hccmentioning
confidence: 99%